An investigation on magnetic imaging findings of the inner ear: A relationship between the internal auditory canal, its nerves and benign paroxysmal positional vertigo - Ergen, Burhan; Baykara, Murat; Polat, Cahit (Elsevier Sci Ltd, 2014)
Visualization of the inner ear has been performed using magnetic resonance imaging (MRI) to investigate benign paroxysmal positional vertigo (BPPV). In the patients with BPPV, our recent findings indicate the thickness of some internal auditory canal (IAC) nerves narrower than the thickness of healthy subjects. The thickness of the IAC and its nerves are measured using brain MRI images. The cross sectional area (CSA) of a nerve is assumed as its thickness. Some statistical measurement and a statistical classification are performed on the CSA data to investigate any relation between IAC, the nerves and BPPV. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Magnetic resonance imaging; Inner ear; Internal auditory canal; Benign paroxysmal positional vertigo